2020
DOI: 10.1002/widm.1381
|View full text |Cite
|
Sign up to set email alerts
|

An overview of unsupervised drift detection methods

Abstract: Practical applications involving big data, such as weather monitoring, identification of customer preferences, Internet log analysis, and sensors warnings require challenging data analysis, since these are examples of problems whose data are generated in streams and usually demand real-time analytics. Patterns in such data stream problems may change quickly. Consequently, machine learning models that operate in this context must be updated over time. This phenomenon is called concept drift in machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Iwashita and Papa (2018) found that unsupervised drift detectors only make up 3% of developed concept drift detectors. However, as Gemaque et al point out, many of the real-world problems are better suited for unsupervised drift detection, since the swift acquisition of labels is often not possible (Gemaque et al, 2020). Since concept drift detection requires fast detection to enable rapid recovery after drift, the topic of unsupervised concept drift detection requires more attention.…”
Section: Unsupervised Concept Drift Detectionmentioning
confidence: 99%
“…Iwashita and Papa (2018) found that unsupervised drift detectors only make up 3% of developed concept drift detectors. However, as Gemaque et al point out, many of the real-world problems are better suited for unsupervised drift detection, since the swift acquisition of labels is often not possible (Gemaque et al, 2020). Since concept drift detection requires fast detection to enable rapid recovery after drift, the topic of unsupervised concept drift detection requires more attention.…”
Section: Unsupervised Concept Drift Detectionmentioning
confidence: 99%
“…Besides these review papers in the literature, other papers explored handling concept drift in specific learning tasks. A recently published review paper by Gemaque et al [42] provides a full-scale overview of the methods that handle concept drift in unsupervised learning. Other papers review and scrutinize the progress in class-imbalanced data streams [43,4].…”
Section: Contextual-based Detectionmentioning
confidence: 99%
“…Several models addressing concept drift on adaptive windows were proposed in recent years. Detailed overviews are given by the work of Iwashita et al [5], Lu et al [6], as well as Gemaque et al [21]. The Learn++.NSE algorithm [22,23] and its fast version [24] generate a new classifier for each received batch of data, and add the classifier to an existing ensemble.…”
Section: Related Work: Concept Drift With Adaptive Shifting Windowsmentioning
confidence: 99%